The Implementation of the Mukhabarah Contract and Its Impact on Farmers’ Well-being in Mallongilongi Village - Wanda Wulandari; Muh. Alim Fasieh; H. Mukhtar Yunus; Jumaedi Nagga (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of the mukhabarah contract and its impact on farmers’ welfare in Mallongilongi Village. The background of this study is based on the discrepancy between profit-sharing practices in the field and the principles of justice in Islamic economics. This study employs a qualitative approach using a case study design. Data were collected through observation and interviews, then analyzed descriptively. The results indicate that mukhabarah practices are still dominated by verbal agreements without clear documentation, potentially leading to a lack of transparency in profit-sharing. Additionally, a tendency toward profit-sharing that is not yet fully fair was identified, which impacts the low level of well-being among some farmers. From an Islamic economic perspective, these conditions do not yet reflect the principles of justice, balance, and public interest. Strengthening the understanding of Sharia contracts and improving the profit-sharing system to make it fairer are necessary, and these should serve as the foundation for further research.